Comparative assessment of Ionic Liquid-Based soft actuators prepared by film casting versus direct ink writing - Correia, Daniela M. (2021)
The growing demand for improved performance, miniaturization and more environmental friendlier devices lead to the search for better materials and processing techniques. Ionic liquid-polymer hybrid materials allow the development of advanced materials suitable for sensors and actuators compatible with additive manufacturing techniques, allowing reduced materials waste and the fabrication of materials in a variety of shapes. In this work, ionic liquids (ILs) blended with poly(vinylidene fluoride) (PVDF) were prepared by doctor blade and direct ink writing. The selected ILs were 1-butyl-3-methylimidazolium dicyanamide [Bmim][N(CN)2] and 1-butyl-3-methylimidazolium thiocyanate [Bmim][SCN], based on their high conductivity value. The effects on microstructure, morphology, thermal, mechanical and electrochemical properties were evaluated, together with the actuator bending. It is shown that the printing process limits the PVDF spherulites growth, leading to lower degrees of crystallinity, which increase the ionic conductivity of the samples. The electromechanical measurements demonstrate the suitability of the developed samples to be applied as actuators, the highest displacement (7.5 mm) being obtained for [Bmim][N(CN)2]/PVDF for an applied voltage of 4 Vpp at a frequency of 0.1 Hz. The large bending (2%) is in line with the best results in the literature, confirming the suitability of printing technologies for the fabrication of high-performance soft actuators.